Knowledge-Based Country Programs : An Evaluation of World Bank Group Experience - Independent Evaluation Group (World Bank Group, Washington, DC, 2014)
This evaluation assesses knowledge-based activities in nine country programs selected from 48 knowledge-intensive programs supported by the Bank Group. It identifies the factors in the success or failure of those activities as they contribute to policy making or development outcomes. It also identifies areas of strength for the Bank Group as well as areas of weakness or risk. The evaluation findings are therefore relevant to current Bank Group efforts to strengthen the contribution of knowledge to development. In addition, the evaluation assessed International Finance Corporation (IFC) advisory services for their synergy with the Bank's analytical and advisory activities. The main objective of the evaluation is to learn lessons from practices in a focus group of high-income and upper-middle-income countries that have knowledge based programs with the Bank Group. This report is organized in five chapters as follows: chapter one is introduction. Chapter two reviews the relevance and strategic positioning of the World Bank in knowledge-based partnerships. Chapter three reviews the technical quality of the knowledge services delivered. Chapter four evaluates the results of the knowledge activities and their sustainability, as well as the synergy between World Bank knowledge services and IFC advisory services in promoting private and financial sector development. Chapter five draws conclusions and discusses the lessons learned from the evaluation.